Real-Time Interrogation of Optical Sensors Based on Wavelength-to-Time Mapping - Deng, Hong (Université d'Ottawa / University of Ottawa, 2018)
Theoretical and experimental studies of real-time interrogation of optical sensors based on wavelength-to-time (WTT) mapping are presented. The sensing information is encoded in the spectrum of an optical sensor, and transferred to the time domain by using WTT mapping. Utilizing digital electronics for post processing, the sensing information can be interrogated at an ultra-high speed and resolution. Two sensors based on WTT mapping are proposed and demonstrated. First, a random grating sensor for simultaneous measurement of the temperature and strain is investigated. An ultra-short pulse from a mode-lock laser is spectrum shaped by a high-birefringence random grating to generate two orthogonally polarized spectrums, which are then fed to an optical loop in which a linearly chirped fiber Bragg grating is incorporated. Linear WTT mapping is implemented, and two temporally separated optical pulses are generated, and then converted to two electrical waveforms at a photodetector. Pulse compression is then employed. By measuring the temporal intervals of the temporally compressed pulses, the strain and temperature information can be retrieved. Conventional fiber based sensors are not sensitive to the refractive index change of the environment. In the second sensor, a silicon photonic microdisk resonator (MDR) for temperature and liquid refractive index sensing is proposed and demonstrated. By using the notches in the spectrum of the MDR, a microwave photonic filter (MPF) is implemented. By feeding a linearly chirped microwave signal to the MPF, a filtered signal with its temporal location representing the spectrum is generated. By monitoring the time location of the filtered signal, the temperature or the refractive index information is revealed.
Keywords: Optical Sensors; Microwave Photonics